Expression of CyclinD1, CDC25B and p27 protein in gastric carcinoma And it s clinical significance - Jun, Wang (Asian Journal of Medical Sciences, 2021)
Background: Gastric cancer is a common digestive tract tumor in our China, with high morbidity and mortality. Similar with other tumors, the occurrence of gastric cancer was also a complex pathophysiological process, regulated by a variety of oncogenes and tumor suppressor gene. Aims and Objectives: This study aims to investigate the expression of cyclin D1, CDC25B, and p27 in gastric carcinoma and to study their relationship with the occurrence and development of gastric cancer. Materials and Methods: SP immunohistochemical and Western blot analysis were used to detect the expression of cyclin D1, CDC25B, and p27 in 42 cases of gastric carcinoma, 42 cases of paracancer, and 42 cases of normal gastric tissue and then their relationship with clinical and pathological factors was analyzed. Results: (1) The expression of cyclin D1 increased gradually in normal gastric tissue, paracancer, and gastric carcinoma (P>0.05). The expression of CDC25B was higher in gastric carcinoma (P<0.05) while p27 was lower (P<0.05). (2) The result of Western blot shows that the expression of cyclin D1 and CDC25B was higher in gastric carcinoma than that in normal gastric tissue while p27 lower in gastric carcinoma (P<0.05), same with immunohistochemical. (3) The expressions of cyclin D1 and CDC25B had correlation with lymph nodes metastasis, and p27 had correlation with degrees of pathological differentiation, invasion depth, and lymph nodes metastasis. (4) There was a positive relationship between the expression of cyclin D1 and CDC25B in same sample (r=−0.392, P<0.05). Conclusion: Expression of cyclin D1, CDC25B, and p27 protein can be helpful in the prediction of the biological behavior and prognosis of gastric carcinoma.